PENGARUH PENGGUNAAN MODEL PROBLEM BASED LEARNING TERHADAP KETERAMPILAN MENULIS TEKS LAPORAN HASIL OBSERVASI - Ermawati Arief, Sieska Afriani, Atmazaki, (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
This research is aimed to describe the influence of problem based learning model towards the skills of wriring the observation report on 7th grader students in SMP Negeri 24 Padang. It was quantitative research and using experiment method. This research was designed using two groups-static. The instrument of this research was performance test and the data was collected using the same test. The data used in this research was the score of performance test from writing the observation report. Based on the result, the use of problem based learning model affects the skills of writing the observation report on 7th grader students in SMP Negeri 24 Padang.Â Kata kunci: model problem based learning, keterampilan menulis, taks laporan hasil observasi